Giant Malignant Phyllodes Tumor in a 36-year-old Female: A Rare Case Report - Betty, Betty; Hasibuan, Arie Widiansyah; Siregar, Denny Rifsal (Indonesian Journal of Cancer, 2025)
Introduction: Phyllodes tumor (PT) is infrequent among breast neoplasms, representing less than 1% of all breast neoplasms, with 10% to 30% of them being malignant. The occurrence rate of malignant phyllodes tumor (MPT) is about 2.1 cases per million people.Case Presentation: We report the case of a 36-year-old female who had a significant mass in her right breast. Macroscopically, the cut surface was grayish-white with cystic areas containing a hemorrhagic mass; the tumor occupied nearly the entire breast with indistinct borders. The tumor measured 26 x 16 x 11 cm. Microscopically, the tumor exhibited a solid structure with ductal proliferation and hypercellular stroma forming a leaf-like appearance. Proliferation of fibrous connective tissue with dysplastic cell morphology and atypical mitoses was found in 10/10 high-power fields (HPFs). Malignant heterologous components included bone matrix with osteoclast-like giant cells and chondroid components. Immunohistochemical Ki-67 staining was positive in more than 20% of the cell nuclei.Conclusion: The tumor is large with unclear infiltration boundaries and contains malignant heterologous components. Immunohistochemical Ki-67 staining was positive in more than 20% of the cell nuclei, confirming this as a case of malignant phyllodes tumor. This case is notable due to its rarity, frequent recurrence, and the challenges in establishing a diagnosis and treatment regimen.